Isolated congenital absence of left circumflex mimicking single coronary artery: A rare coronary anomaly case report - Ramadhan, Fitri Febrianti; Saskia Dyah Handari (Universitas Brawijaya, 2026)
Background: Congenital coronary artery anomalies (CAAs) occur in roughly 1% of the population and, while often incidental, are recognized contributors to sudden cardiac death, particularly in younger individuals. Many anomalies remain silent until adulthood. Case Presentations: A 59-year-old man with obesity, hypertension, and heavy tobacco use presented with exertional dyspnea and recurrent chest pain radiating to the left arm and neck. Initial evaluation showed normal high-sensitivity troponin, an unremarkable electrocardiography (ECG), and a normal transthoracic echocardiogram; his clinical likelihood of obstructive coronary artery disease was estimated at Chronic Coronary Syndrome (CCS) Risk Factor-weighted Clinical Likelihood (RF-CL) 27%. Coronary CT angiography (CCTA) demonstrated congenital absence of the left circumflex artery (LCx) with a super-dominant right coronary artery (RCA) coursing subaortically to supply the lateral wall. A non-obstructive calcified plaque was identified in the proximal left anterior descending artery, with an Agatston calcium score of approximately 145, indicating quantifiable but moderate atherosclerotic burden. The distinction between a single coronary artery (SCA) and an absent LCx is clinically important. In SCA, all coronary branches originate from a single aortic ostium, whereas in absent LCx, there is no separate LCx ostium, and the RCA (and occasionally enlarged diagonal branches) perfuses the LCx territory; CCTA is pivotal for depicting ostial origin and vessel course. The patient was treated with a beta-blocker, an angiotensin-converting enzyme inhibitor, a statin, and aspirin. Conclusions: Given persistent symptoms, functional testing is recommended to determine ischemic significance and guide management. Accurate identification of this subtle anomaly and comprehensive risk stratification are essential to optimize outcomes.